2013
DOI: 10.1128/jvi.00757-13
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in Dengue Virus When Exposed to a Temperature of 37°C

Abstract: Previous binding studies of antibodies that recognized a partially or fully hidden epitope suggest that insect cell-derived dengue virus undergoes structural changes at an elevated temperature. This was confirmed by our cryo-electron microscopy images of dengue virus incubated at 37°C, where viruses change their surface from smooth to rough. Here we present the cryo-electron microscopy structures of dengue virus at 37°C. Image analysis showed four classes of particles. The three-dimensional (3D) map of one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
198
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 174 publications
(218 citation statements)
references
References 27 publications
17
198
1
2
Order By: Relevance
“…Recent studies on DENV--2 detected a particle expansion at physiological temperatures of humans, causing the E dimers to reorient with respect to each other and presenting a different surface pattern as in mosquito grown viruses 27,28 . bnAbs targeting the EDE will neutralize regardless of the surface arrangement of E dimers.…”
Section: Igkv3--11 (Ede1 C8 the Patient Appeared To Have A Primary mentioning
confidence: 99%
“…Recent studies on DENV--2 detected a particle expansion at physiological temperatures of humans, causing the E dimers to reorient with respect to each other and presenting a different surface pattern as in mosquito grown viruses 27,28 . bnAbs targeting the EDE will neutralize regardless of the surface arrangement of E dimers.…”
Section: Igkv3--11 (Ede1 C8 the Patient Appeared To Have A Primary mentioning
confidence: 99%
“…Previous studies of interactions of DENV2 with antibodies demonstrated that the usually inaccessible parts of its shell proteins could be exposed when the incubation temperature is raised to 37°C (10,11). Also, cryo-electron microscopy (cryo-EM) reconstruction of DENV2 particles that were incubated at 37°C showed that the particles had expanded and acquired a bumpy surface (12,13).…”
mentioning
confidence: 99%
“…This can affect the accessibility of some antigenic sites which may be occluded in some conformations but exposed in others and explains why binding of some antibodies may be enhanced by prolonged incubation or by increased temperature 13 . A "bumpy" conformation of DENV2 has been described in which the virus particle is expanded and the interaction of the 90 E-dimers is changed relative to the standard mature virus particle which may disrupt some quaternary epitopes formed between opposing dimers 14,15 . It is interesting in this regard that the Zika virus (ZIKV) particles seem to be relatively more rigid than DENV particles 16,17 .…”
Section: Structural Flexibility Of the Dengue Virionmentioning
confidence: 99%